The beautiful risk of music education: exploring the pedagogical risks and possibilities of gender and sexuality in music education - Eirik Skjelstad (Nordic Research in Music Education)
This article investigates the potential risk of addressing topics related to gender and sexuality within Norwegian music education for primary and lower-secondary public school, rooted in Gert Biesta’s (2016) notion of “the beautiful risk of education”. The article examines the position of music education in fostering discussions on gender roles and sexuality in Norway, emphasizing how these topics challenge traditional teaching norms and encourage critical engagement among students. The article highlights the potential risk and discomfort involved in such educational settings, proposing that navigating these challenges is crucial for developing inclusive educational practices that acknowledge and include diverse identities and perspectives. The article calls for more research to deepen understanding and improve the implementation of these critical pedagogical approaches across various cultural contexts, suggesting that music education can serve as a dynamic platform for broader social and cultural engagement.